Evolution of the application of system of till of soil after method of T. S. Maltsev in Ukraine in 1954–1955 - N. P. Kovalenko (History of science and technology, 2018)
Basic conformities to law and tendencies of application of the system of till of soil have been set after the method of Terentij Semen Maltsev in Ukraine in 1954–1955. The role of the collective farm experimental stations has been reflected in the productive experiments execution and research establishments in realization of the ground and agrochemical researches in relation to efficiency of application of the system of till of soil without dumps in sowing of different agricultural cultures of Steppe, Forest-Steppe and Polesye of Ukraine.